What Does Brain Research Say about Teaching and Learning Mathematics? - Allan Leslie White (SEAMEO Regional Centre for QITEP in Mathematics, 2012)
Brain research has shaken our ideas of the structure of the brain and how the brain works. Gone are the ancient ideas of comparing the brain to a machine. Neuroplasticity describes the remarkable ways in which the brain adapts and transforms itself as a result of a change in stimuli. Cognitive exercises have been designed and trialled that improve memory, problem solving abilities, and language skills in aged subjects and in children, as well as reversing the aging process by twenty to thirty years in some adults. Since the decline of behaviourism as a major theoretical influence upon mathematics education, there have been a number of learning theories emphasising thinking and the influences of the social and cultural contexts. Although, brain research is in its infancy, the question arises as to what does brain research add to mathematics teaching and learning in addressing student needs and developing their potential?